The determinants of internet financial disclosure: The perspective of Malaysian listed companies - Alarussi, Ali Saleh; Selamat, Mohamad Hisyam; Mohd Hanefah, Mustafa (Universiti Utara Malaysia, 2011)
This paper investigates whether Internet Financial Disclosure (IFD) can be explained by the elements of the company’s characteristics and dominant personalities in board committees.Ten variables have been tested using data collected from 194 Malaysian listed companies’ websites, namely, internationality, leverage, foreign shareholders, information technology (IT) experts, firm’s age, number of shareholders, listing status, dominant personalities in the audit committee, chairman of audit and nomination committees, and dominant personalities in the audit and nomination committees.It is found that IT experts, firm’s age, number of shareholders and listing status are significantly affected by the level of IFD. However dominant personalities in the audit and nomination committees are negatively related to the level of IFD in Malaysia.The study provides some evidence to support the signalling theory and the cost and benefit hypothesis in relation to Internet disclosure.